Pedagogy for Hopeful Futures: Reimagining Social Innovation and Entrepreneurship Education - Raible, Stephanie; Pattermann-Gunsch, Juliana; Vögele, Julia; Wieser, Desiree (Tidsskrift for Social Innovation & Transformativ Entreprenørskabsdidaktik (SITE), 2026)
Faced with ecological, economic, and social crises conceptualized as wicked problems and polycrises, students in social innovation and entrepreneurship (SIE) classrooms often adopt analytical orientations that privilege critique over solution-building. This article introduces hopeful futures as a pedagogical orientation that connects futures literacy (FL) with students’ agency and capacity to act. Hopeful futures are defined as desirable imaginaries regarded as possible and actionable, integrating plural understandings of futures with hope as agency for intentional change. The article situates hopeful futures within SIE education by examining the roles of hope and FL, reviewing competence frameworks including Catalyst Now, EntreComp, GreenComp, and Ploum and colleagues, and identifying implicit and explicit references to hope and futures-oriented capabilities. It argues that cultivating hopeful dispositions enables students to navigate uncertainty, strengthen resilience, and engage creatively with complexity. Practices such as design-based learning, collective reflection, and the Futures Literacy Lab foster imaginative agency, empathy, and co-creation, supporting socially responsible innovation. Embedding hopeful futures within SIE pedagogy advances systemic change, strengthens students’ capacity to envision and pursue preferable futures, and positions FL as a foundation for cultivating future-oriented social innovation.